2020
DOI: 10.3390/su122310074
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Students’ and Parents’ Perceptions of Authentic Contextual Learning at Home and Their Mutual Influence on Technological and Pedagogical Aspects of Learning under COVID-19

Abstract: During the COVID-19 pandemic, students have been forced to learn at home. Authentic contexts are essential to designing useful learning activities. Therefore, this study used mobile technology, namely Ubiquitous Geometry (UG), to merge authentic contexts into learning activities and investigate the influence of authentic contextual learning (ACL) on students’ and parents’ perceptions. This is because parents inevitably have an effect on students’ learning at home, which has not been clearly addressed in past s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Regarding the fourth research question, the students' felt that RoamLingo was useful to help them to learn EFL writing anytime and anywhere using mobile phones with AI and recognition technologies. The students have strong motivation to complete their essay by exploring their surroundings even in covid-19 pandemic situations (Hwang & Hariyanti, 2020). It is because they got inspiration from the contexts in their surroundings with AI-SS.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the fourth research question, the students' felt that RoamLingo was useful to help them to learn EFL writing anytime and anywhere using mobile phones with AI and recognition technologies. The students have strong motivation to complete their essay by exploring their surroundings even in covid-19 pandemic situations (Hwang & Hariyanti, 2020). It is because they got inspiration from the contexts in their surroundings with AI-SS.…”
Section: Discussionmentioning
confidence: 99%
“…It is in accordance with a study by (Mutambara & Bayaga, 2020) that when parents have positive feelings towards online counseling services, these feelings will strengthen their intention to allow their children to carry out online counseling services for self-development. Hwang & Hariyanti (2020) found that parents believe that the use of mobile devices is beneficial for learning, but they are worried about excessive use at the same time. This means that even though parents have knowledge about the benefits of online counseling services for self-development, concerns about increasing internet quota cost affect their attitudes towards online counseling services.…”
Section: Discussionmentioning
confidence: 99%
“…These simulated encounters foster greater cultural understanding and empathy [18,30]. Furthermore, technology-driven platforms, such as online discussion forums, video conferencing, and collaborative workspaces, enable learners from diverse cultures to collaborate, communicate, and exchange ideas seamlessly [11,20,[31][32][33][34]. By overcoming geographical barriers, these platforms facilitate real-time interactions, nurturing cross-cultural comprehension and promoting teamwork [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%